2016
DOI: 10.1111/1346-8138.13551
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of IL36RN gene in Japanese patients with palmoplantar pustulosis

Abstract: Loss-of-function mutations of the IL36RN gene, encoding interleukin-36 receptor antagonist (IL-36Ra), have been reported as major pathogenic causes of generalized pustular psoriasis (GPP), especially in cases lacking previous histories of psoriasis vulgaris. Palmoplantar pustulosis (PPP), which is traditionally included among GPP-related diseases, has a controversial association with IL36RN. While a negative view about the said association has been recently published from Europe, variations of the IL36RN gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…In contrast, Mössner et al found four patients with heterozygous IL36RN variants who were without pathogenicity among 251 PPP patients, which suggested that PPP was not associated with loss-of-function IL36RN mutations in Europeans 8 . Takahashi et al found four of 88 Japanese PPP patients had heterozygous IL36RN variants, and similarly concluded that these variants did not seem to be associated with the phenotype of PPP 7 . The different results in these reports may reflect the different ethnicities of the study populations.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In contrast, Mössner et al found four patients with heterozygous IL36RN variants who were without pathogenicity among 251 PPP patients, which suggested that PPP was not associated with loss-of-function IL36RN mutations in Europeans 8 . Takahashi et al found four of 88 Japanese PPP patients had heterozygous IL36RN variants, and similarly concluded that these variants did not seem to be associated with the phenotype of PPP 7 . The different results in these reports may reflect the different ethnicities of the study populations.…”
Section: Discussionmentioning
confidence: 97%
“…IL36RN may have no association with the clinical manifestation of PPP. Another piece of evidence is that the skin lesions of heterozygous IL36RN PPP patients stained positively for IL-36Ra in an immunohistochemical analysis, showing no difference with normal controls 7 . Moreover, Onoufriadis et al concluded that three GPP patients had homozygous (p.Ser113Leu) or compound heterozygous mutations (p.Ser113Leu, p.Arg48Trp), but no mutation was observed in another two GPP patients with PPP complications 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study on 57 Chinese patients with pustular psoriasis, IL36RN mutations were found in 75% of GPP patients and 94% of ACH patients [ 21 ]. On the contrary, Takahashi and colleagues performed mutation analysis of the IL36RN gene in 88 Japanese patients with PPP and identified three types of single base substitutions of IL36RN; they were heterozygous and different from those found in European studies, and they were considered to be of no pathogenic relevance [ 22 , 23 ]. Furthermore, other studies in patients with PPP have shown that the combined frequency of AP1S3 and IL36RN mutations accounts for less than 10% of patients, suggesting not only that PPP is not clearly associated with IL36RN but also that known genes account for only a minority of disease cases [ 17 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because the deficiency of IL-36R antagonist appears to be associated with various autoimmune diseases, 15 , 17 , 19 , 20 the underlying mechanism might be a dysfunction in controlling the basal activity of IL-36R signaling. This was supported by the finding that, unlike IL-1, IL-36 cytokines have basal expression in unchallenged tissues and cells.…”
mentioning
confidence: 99%